2015
DOI: 10.1103/physrevlett.114.197001
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Charge-Density-Wave and Pair-Density-Wave Orders in Underdoped Cuprates

Abstract: We analyze incommensurate charge-density-wave (CDW) and pair-density-wave (PDW) orders with transferred momenta (±Q, 0)/(0, ±Q) in underdoped cuprates within the spin-fermion model. Both orders appear due to exchange of spin fluctuations before magnetic order develops. We argue that the ordered state with the lowest energy has non-zero CDW and PDW components with the same momentum. Such a state breaks C4 lattice rotational symmetry, time-reversal symmetry, and mirror symmetries. We argue that the feedback from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 63 publications
12
103
0
2
Order By: Relevance
“…However, as we increase the cou-plings to somewhat moderate interactions, we do find a tendency for PDW/CDW to become leading compared to BDW/SSC near the HSFP obtained in the present work. This last result would in principle agree with the experimental situation, in which the leading charge order that emerge in non-Lanthanum-based cuprates has indeed a modulation determined by Q x(y) .Therefore, it seems reasonable to speculate here that this new emergent SU (2) symmetry relating PDW and CDW may indeed have profound consequences for the physics of the underdoped cuprates, as has been recently alluded to by many authors in the literature [30][31][32]55 .…”
Section: B Two Loop Rgsupporting
confidence: 83%
“…However, as we increase the cou-plings to somewhat moderate interactions, we do find a tendency for PDW/CDW to become leading compared to BDW/SSC near the HSFP obtained in the present work. This last result would in principle agree with the experimental situation, in which the leading charge order that emerge in non-Lanthanum-based cuprates has indeed a modulation determined by Q x(y) .Therefore, it seems reasonable to speculate here that this new emergent SU (2) symmetry relating PDW and CDW may indeed have profound consequences for the physics of the underdoped cuprates, as has been recently alluded to by many authors in the literature [30][31][32]55 .…”
Section: B Two Loop Rgsupporting
confidence: 83%
“…Recent work by Agterberg and Garaud further showed that for competing dSC and PDW, a vortex core will favor PDW through the suppression of dSC, and also drive complementary charge modulation, as those seen in experiments 26 . After the observation by Lee that some photoemission results in cuprates agree better with a PDW scenario than with one based on charge density waves 27 , and after much work stating how many theoretical models are prone to several forms of PDWs [28][29][30][31][32] , experimental evidence of pair density wave was finally obtained, at zero-field, for an underdoped sample of BSCCO, through scanning Josephson tunneling spectroscopy 33 . It would be hard, at this point, to exclude PDWs from the cuprate puzzle.…”
Section: Introductionmentioning
confidence: 99%
“…This order has been proposed in several theory papers [30][31][32][33][34][35][36] and was recently reported to be observed in the tunneling experiments on the cuprates 37 .…”
Section: Introductionmentioning
confidence: 97%
“…The PDW order is a superconducting order with a non-zero total momentum of a pair (like in Fulde-Ferrel-Larkin-Ovchinnikov (FFLO) state, but in zero field). Signatures of the PDW order has been detected in the tunneling experiments on the cuprates 37 , and PDW order has been obtained in various analytical [30][31][32][33][34][35][36][42][43][44] and numerical 45 theoretical calculations. It was argued that the presence of a PDW order explains several experimental features in the pseudogap phase [30][31][32]35 .…”
Section: The Effect Of the Pdw Ordermentioning
confidence: 99%